Pengaruh Variasi Temperatur Preheating Pada Pengelasan Gas Metal Arc Welding (GMAW) Baja SM490 Terhadap Sifat Mekanik Dan Struktur Mikro - Andeliani Saputri; Agris Setiawan (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
The railway industry is a manufacturing industry engaged in the manufacture, repair, and maintenance of trains. In the train manufacturing process, one of the components of the train structure is the train bogie. Train bogies are generally made using SM490 Steel material because they have good strength, toughness, machinability, and weldability. The manufacture of bogies is generally done by welding methods. One of the commonly used welding methods is Gas Metal Arc Welding (GMAW). This study aims to determine the effect of the preheating process on the mechanical properties and microstructure of the welding results. Data obtained from tests including hardness testing, tensile testing, impact testing, and microstructure observations. Hardness testing shows a decrease in the strength value of the welding results where the highest value is obtained in untreated material of 179.53 HVN and the lowest value in material with 300˚C preheating of 172.23 HVN. Tensile test data shows an increase in tensile strength by applying the preheating process, where the highest tensile strength and elongation values ​​were obtained in the material with 200˚C preheating, namely 536.1 MPa with an elongation of 18.9%. Impact test data shows an increase in toughness in the material with preheating treatment. Microstructural observation data shows a change in the microstructure in the weld metal area. It was also found from the microstructural observations that the ferrite phase dominates.